Draft Annual Plan 1994-95 Part - I Volume - II Govt. of National Capital Territory of Delhi - Planning Commission (Planning Commission, 1994)
At present, the hospital bed ratio is 2.06 in Urban and 0.25 per thousand population in Rural area. The basic responsibility for providing adequate Health Care facilities to the people of this Territory lies with Dte. of Health Services. The main thrust of the recent policies and programmes in this field has been to remove the geographical imbalance in the provision of medical services in Delhi by opening new hospitals, dispensaries, poly clinics in rural areas, resettlement colonies and other far-flung areas, expansion of school health schemes, introduction of a number of training courses for para-medical staff, modernisation of all medical laboratories and procurement of modern equipments for existing hospitals.
Planning Department, Govt. of National Capital Territory of Delhi